Influence of game design, physical demands, and skill involvement on the subjective task load associated with various small-sided games among elite junior rugby league players - Dobbin, N.; Atherton, A.; Hill, C. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To determine if small-sided games (SSGs) could be designed to target specific task loads using the National Aeronautics and Space Administration task load index as well as reporting the influence of the physical and technical demands.